Pengaruh Perceived Organizational Support Terhadap Turnover Intention Dengan Job Satisfaction Sebagai Variabel Mediasi Pada PT. BANK MNC DI JAKARTA PUSAT - Felix Herianto; Yanuar Yanuar (Jurnal Manajerial Dan Kewirausahaan, 2021)
this study aims to determine the influence of perceived organizational support on turnover intention through job satisfaction as mediating variable both indirectly or directly. The sample in this study were 75 employees of PT. Bank MNC at Jakarta Pusat, whom the majority are sales divition, a minimum sample is determine by using Hair’s formula which are the indicators times with five. The analysis method used is SmartPLS 3.2.8 resulting in Perceived Organizational Support has a positive and significant effect on job satisfaction. Job satisfaction has a negative and not significant effect on turnover intention. Perceived organizational support has a negative and not significant effect on turnover intention. And perceived organizational support has a negative and not significant effect on turnover intention through job satisfaction as a mediating variable. The implication of this research is that the company is expected to increase perceived organizational support for employees to increase job satisfaction, then the next research party is expected to re-examine perceived organizational support for turnover intention, job satisfaction with turnover intention and perceived organizational support for turnover intention through job satisfaction because of the results of this study not significant. this study aims to determine the influence of perceived organizational support on turnover intention through job satisfaction as mediating variable both indirectly or directly. The sample in this study were 75 employees of PT. Bank MNC at Jakarta Pusat, whom the majority are sales divition, a minimum sample is determine by using Hair’s formula which are the indicators times with five. The analysis method used is SmartPLS 3.2.8 resulting in Perceived Organizational Support has a positive and significant effect on job satisfaction. Job satisfaction has a negative and not significant effect on turnover intention. Perceived organizational support has a negative and not significant effect on turnover intention. And perceived organizational support has a negative and not significant effect on turnover intention through job satisfaction as a mediating variable. The implication of this research is that the company is expected to increase perceived organizational support for employees to increase job satisfaction, then the next research party is expected to re-examine perceived organizational support for turnover intention, job satisfaction with turnover intention and perceived organizational support for turnover intention through job satisfaction because of the results of this study not significant..